2020
DOI: 10.1002/1438-390x.12064
|View full text |Cite
|
Sign up to set email alerts
|

Linking Ocean's Benefits to People (OBP) with Integrated Ecosystem Assessments (IEAs)

Abstract: The fundamental challenge of the inclusion of the human dimension of the oceans in the Integrated Ecosystem Assessments (IEAs) provides an opportunity for a transdisciplinary approach to create synergies between the current research by the International Council for the Exploration of the Sea (ICES) and the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES). We have highlighted the importance of ocean inequality as a critical aspect to consider to unlock current barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…75,74,76,77 This diagnosis will help to understand who is marginalized, hierarchies of decision-making power, access to benefits or cash, and thus how the livelihood approach will support or disrupt these hierarchies, and with what implications. 78 The outcome of fair and just livelihoods interacts with other outcomes and will require decisions about trade-offs. For instance, a key consideration for coastal livelihoods in the Pacific is the rights of individuals or groups over land and sea associated with existing customary tenure systems.…”
Section: Fair and Just Livelihoodsmentioning
confidence: 99%
“…75,74,76,77 This diagnosis will help to understand who is marginalized, hierarchies of decision-making power, access to benefits or cash, and thus how the livelihood approach will support or disrupt these hierarchies, and with what implications. 78 The outcome of fair and just livelihoods interacts with other outcomes and will require decisions about trade-offs. For instance, a key consideration for coastal livelihoods in the Pacific is the rights of individuals or groups over land and sea associated with existing customary tenure systems.…”
Section: Fair and Just Livelihoodsmentioning
confidence: 99%
“…When reading both the definitions together human dimensions are intrinsically included in the ecosystem conceptualization. For this study a fuller definition of EBM is considered which includes both a transboundary management component and the human dimensions of ecosystems (Alexander et al, 2018;Belgrano and Villasante, 2021). The TWAP (Fanning et al, 2015;Mahon et al, 2015) observed that the BCC had a structured governance arrangement with an established Commission.…”
Section: Polycentricity Good Governance and Effective Governance For Ecosystem-based Managementmentioning
confidence: 99%
“…For example, a global study recently found that natural protected areas received eight billion visitors a year, generating up to an estimated USD$600 billion, making it approximately 8% of the travel and tourism market in 2015 (Balmford et al, 2015). MPAs also need to incorporate Blue Justice in accordance with various UN principles (e.g., FAO, 2015) and Agenda, 2030 (Colglazier, 2015;United Nations, 2020) and thus to ensure equitable distribution of multiple monetary and nonmonetary benefits and values they provide (Belgrano and Villasante, 2020;Jentoft, 2020), in particular in relation to vulnerable coastal based communities and other social groups (Lopes and Villasante, 2018).…”
Section: Introductionmentioning
confidence: 99%